Atipamezole, a specific alpha(2A) antagonist, suppresses spike-and-wave discharges and alters Ca2+/calmodulin-dependent protein kinase II in the thalamus of genetic absence epilepsy rats - AYDIN OMAY, BANU; ONAT, FİLİZ; YANANLI, HASAN RACİ (WILEY, 2020)
Objective The role of alpha(2A) adrenergic receptors (alpha(2A)ARs) in absence epilepsy is not well characterized. Therefore, we investigated the outcomes of the specific antagonism of alpha(2A)ARs on the spike-and-wave discharges (SWDs) in genetic absence epilepsy rats from Strasbourg (GAERSs), together with its influence on the behavior and second messenger systems, which may point to the mechanisms to which a possible SWD modulation can be related. Methods Atipamezole, an alpha(2A)AR antagonist, was administered intracerebroventricularly to the adult GAERSs, and electroencephalography (EEG) was conducted. The cumulative duration and number of SWDs, and the mean duration of each SWD complex were counted. The relative power of the EEG frequency bands and behavioral activity after the acute application of two doses (12 and 31 mu g/5 mu L) of atipamezole were evaluated. The levels of cyclic adenosine monophosphate and calcium/calmodulin-dependent kinase II (CaMKII) were measured in the cortex, thalamus, and hippocampus of naive Wistar rats and GAERSs, administered with artificial cerebrospinal fluid (aCSF) as a vehicle, or either acute or chronic atipamezole (12 mu g), the latter being administered for 5 consecutive days. Results Atipamezole significantly suppressed SWDs dose-dependently, without affecting the relative power values of EEG frequency spectrum. The stereotypic activity was significantly lower in both naive Wistar rats and GAERSs receiving the highest dose (31 mu g) of atipamezole compared to GAERSs receiving aCSF. In GAERSs, CaMKII levels were found to be higher in the thalamus after the acute and chronic application of SWD-suppressing doses of atipamezole (12 and 31 mu g) compared to aCSF. Significance This study emphasizes the alpha(2)AR-related modulation of absence epilepsy and particularly the significance of alpha(2)AR antagonism in suppressing SWDs. Atipamezole's SWD-suppressive actions may be through CaMKII-mediated second messenger systems in the thalamus.
Keywords: absence epilepsy; alpha‐ adrenergic receptor 2A; CaMKII; GAERS; stereotypic activity; SWDs; ALPHA(2)-ADRENOCEPTOR ANTAGONIST; SEIZURES; RECEPTOR; CORTEX; MODEL; EEG; NEUROTRANSMISSION; BEHAVIOR; SUBTYPE; ANXIETY